Endoscopic Ultrasound Fine-Needle Aspiration versus Fine-Needle Biopsy for Lymph Node Diagnosis: A Large Multicenter Comparative Analysis - Diogo Turiani Hourneaux de Moura; Thomas R. McCarty; Pichamol Jirapinyo; Igor Braga Ribeiro; Galileu Ferreira Ayala Farias; Marvin Ryou; Linda S. Lee; Christopher C. Thompson (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Endoscopic ultrasound fine-needle aspiration (EUS-FNA) is preferred for sampling of lymph nodes (LNs) adjacent to the gastrointestinal wall; however, fine-needle biopsy (FNB) may provide improved diagnostic outcomes. This study aimed to evaluate the comparative efficacy and safety of FNA versus FNB for LN sampling. Methods This was a multicenter retrospective study of prospectively collected data to evaluate outcomes of EUS-FNA and EUS-FNB for LN sampling. Characteristics analyzed included sensitivity, specificity, accuracy, the number of needle passes, diagnostic adequacy of rapid on-site evaluation (ROSE), cell-block analysis, and adverse events. Results A total of 209 patients underwent EUS-guided LN sampling. The mean lesion size was 16.22±8.03 mm, with similar sensitivity and accuracy between FNA and FNB ([67.21% vs. 75.00%, respectively, p=0.216] and [78.80% vs. 83.17%, respectively, p=0.423]). The specificity of FNB was better than that of FNA (100.00% vs. 93.62%, p=0.01). The number of passes required for diagnosis was not different. Abdominal and peri-hepatic LN location demonstrated FNB to have a higher sensitivity (81.08% vs. 64.71%, p=0.031 and 80.95% vs. 58.33%, p=0.023) and accuracy (88.14% vs. 75.29%, p=0.053 and 88.89% vs. 70.49%, p=0.038), respectively. ROSE was a significant predictor for accuracy (odds ratio, 5.16; 95% confidence interval, 1.15-23.08; p=0.032). No adverse events were reported in either cohort. Conclusions Both EUS-FNA and EUS-FNB are safe for the diagnosis of LNs. EUS-FNB is preferred for abdominal LN sampling. EUS-FNA+ ROSE was similar to EUS-FNB alone, showing better diagnosis for EUS-FNB than traditional FNA. While ROSE remained a significant predictor for accuracy, due to its poor availability in most centers, its use may be limited to cases with previous inconclusive diagnoses.